Selected Papers from the 1st International Electronic Conference on Biosensors (IECB 2020) - Marrazza, Giovanna; Tombelli, Sara (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The scope of this Special Issue is to collect some of the contributions to the First International Electronic Conference on Biosensors, which was held to bring together well-known experts currently working in biosensor technologies from around the globe, and to provide an online forum for presenting and discussing new results. The world of biosensors is definitively a versatile and universally applicable one, as demonstrated by the wide range of topics which were addressed at the Conference, such as: bioengineered and biomimetic receptors; microfluidics for biosensing; biosensors for emergency situations; nanotechnologies and nanomaterials for biosensors; intra- and extracellular biosensing; and advanced applications in clinical, environmental, food safety, and cultural heritage fields.